Modelling public perception of Rohingya refugees using Structural Equation Modelling (PLS) in Malaysia / Mohd Ramlan Mohd Arshad ... [et al.] - Mohd Ramlan, Mohd Arshad; Ajis, Mohd Na’eim; Khairi, Aizat (Universiti Teknologi MARA, Kedah, 2021)
As every part of the world is battling with the deadly virus, Malaysia is also struggling in flattening the Covid-19 curve with Rohingya refugees being one of the clusters involved. This creates both a positive and negative perception of the Rohingya community in this country. Therefore, this study aims to explore the perception of the public on Rohingya refugees in Malaysia. Public perception is referred to as the process to determine the way people interpreted their surroundings. Apart from that, the objectives are also mainly to identify the relationship between media, knowledge, government policy and competition in job toward the public perception of Rohingya refugees. 384 respondents of this study were community lived in Selayang, Selangor, Malaysia. A purposive sampling technique was used with a questionnaire as the instrument. SEMPLS analysis was conducted and the findings show that there is a significant relationship between the variables and perception of Rohingya refugees with mass media considered as the main factor. This study suggested that public perceptions can be constructed through the tested variables even knowledge can be considered to have a low impact on perception. Hence, various parties such as authority, non-governmental bodies and community has benefited from the study.